Cronologia vieţii literare româneşti 1944–1964 (V) - Andrei Grigor; Lucian Chişu; Andrei Milca (Revista de Istorie și Teorie Literară)
This large stuff represent a cronology of what happen in the writing Romanian publications during the 1950 year, a black period where the litterature was under totalitarian commands and fear. That cronology was elaborated and composed by a groupe of researchers as Andrei Grigor, Lucian Chişu, Andrei Milca.